Weed interference periods in the 'Fécula Branca' cassava - Costa,N.V. (2013)
This study aimed to determine the periods of weed interference in the first cycle of 'Fécula Branca' cassava. The experiment was arranged in a randomized block design, with four repetitions. The treatments consisted of eight periods of weed control (25, 50, 75, 100, 125, 150, and 175 days after planting - DAP) and eight periods of coexistence between the weed community and the crop (25, 50, 75, 100, 125, 150, and 175), besides control without weeds and control with weeds until harvest (322 DAP). The predominant weed species with higher relative importance were: Avena sativa, Sorghum halepense, Conyza Canadensis, Euphorbia heterophylla, Raphanus raphanistrum, and Commelina benghalensis. It was concluded that, accepting losses of 1% for root and starch production, the period before interference (PBI) was 66 and 70 DAP; the total period of interference prevention (TPIP) was 88 and 91 DAP and the critical period of interference (CPI) was between 66-88 and 70-91 DAP, respectively. For losses of 5% for root and starch production, the PBI was 87 and 88 DAP, and the TPIP 80 and 81 DAP, respectively; in this case, there was no CPI. Considering the average prices of R$ 218.90 t-1 and R$ 1,191.84 t-1, paid in 2012 for root and starch production, respectively, and control cost of R$ 300.00 ha-1 , the root and starch production for the period prior to economic loss (WEEPPEL) could be estimated to be 20 and 24 DAP, respectively.